The Role of Financial Literacy, Fomo, and Financial Technology in Invesment Decisions Among Generation Z Students - Adelia Puspita Sari; Sri Trisnaningsih (Economics and Business Journal (ECBIS), 2026)
This study seeks to examine the role of investment decisions among Generation Z students by analyzing the roles of financial literacy, Fear of Missing Out (FOMO), and financial technology. A quantitative approach was employed using primary data collected through questionnaires distributed to Generation Z students. The sample consisted of 89 respondents selected through a random sampling technique. Data analysis was conducted using Partial Least Squares (PLS) with the support of SmartPLS software, including the evaluation of the measurement model, structural model, and hypothesis testing through bootstrapping. The findings reveal that financial literacy, FOMO, and financial technology have positive and significant effects on investment decisions. These results indicate that cognitive factors, such as financial literacy, along with behavioral and technological factors, including FOMO and fintech, play significant roles in shaping investment behavior. This study contributes to the existing literature by providing empirical insights into investment decision-making among Generation Z in the context of financial literacy, psychological influences, and technology adoption.